(untitled) (Research, Society and Development, 2021)
In this work, Jerome Bruner’s theory is emphasized because he understands that Problem Solving is the central point for the construction of human knowledge. This author provides guidance on the child’s development, based on the student’s active participation in the development of his learning process. Thus, it proposes to present and discuss aspects of teaching theory based on the author’s guidelines that deepens the child’s active participation in the development of his learning process, in learning through discovery, in the exploration of new teaching alternatives and in the curriculum spiral, taking into account the child’s developmental stages. In this conception, the author’s theoretical assumptions can allow teacher training that values ​​the cognitive development of individuals.